A novel cyclodione coumarin from the stem bark of Mesua beccariana - Ee, Gwendoline Cheng Lian; Teh, Soek Sin; Mah, Siau Hui; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Awang, Khalijah (MDPI, 2011)
Our ongoing investigations on the stem bark of Mesua beccariana afforded a novel cyclodione coumarin, beccamarin, together with two known xanthones, mesuarianone, mesuasinone, two anthraquinones, 4-methoxy-1,3,5-trihydroxy-anthraquinone and 2,5-dihydroxy-1,3,4-trimethoxyanthraquinone and one coumarin, mammea A/AB. The structures were elucidated by 1D and 2D NMR and MS techniques.